Improved soybean root association of N-starved Bradyrhizobium japonicum - López García, Silvina Laura (2001)
In this study, we addressed the effects of N limitation in Bradyrhizobium japonicum for its association with soybean roots. The wild-type strain LP 3001 grew for six generations with a growth rate of 1.2 day-1 in a minimal medium with 28 mM mannitol as the carbon source and with the N source [(NH4)2SO4] limited to only 20 μM. Under these conditions, the glutamine synthetase (GS) activity was five to six times higher than in similar cultures grown with 1 or 0.1 mM (NH4)2SO4. The NtrBC-inducible GSII form of this enzyme accounted for 60% of the specific activity in N-starved rhizobia, being negligible in the other two cultures. The exopolysaccharide (EPS) and capsular polysaccharide (CPS) contents relative to cell protein were significantly higher in the N-starved cultures, but on the other hand, the poly-3-hydroxybutyrate level did not rise in comparison with N-sufficient cultures. In agreement with the accumulation of CPS in N-starved cultures, soybean lectin (SBL) binding as well as stimulation of rhizobial adsorption to soybean roots by SBL pretreatment were higher. The last effect was evident only in cultures that had not entered stationary phase. We also studied nodC gene induction in relation to N starvation. In the chromosomal nodC::lacZ fusion Bj110-573, nodC gene expression was induced by genistein 2.7-fold more in N-starved young cultures than in nonstarved ones. In stationary-phase cultures, nodC gene expression was similarly induced in N-limited cultures, but induction was negligible in cultures limited by another nutrient. Nodulation profiles obtained with strain LP 3001 grown under N starvation indicated that these cultures nodulated faster. In addition, as culture age increased, the nodulation efficiency decreased for two reasons: fewer nodules were formed, and nodulation was delayed. However, their relative importance was different according to the nutrient condition: in older cultures the overall decrease in the number of nodules was the main effect in N-starved cultures, whereas a delay in nodulation was more responsible for a loss in efficiency of N-sufficient cultures. Competition for nodulation was studied with young cultures of two wild-type strains differing only in their antibiotic resistance, the N-starved cultures being the most competitive.